Photodynamic therapy: A new vista in management of periodontal diseases - Yogesh Doshi; Priya S Patil; Nishat Shah; Santosh Dixit; Mona Shah (Wolters Kluwer Medknow Publications, 2010)
Aim: The purpose of this review was to evaluate the effectiveness of photodynamic therapy (PDT) for periodontitis. This review also elucidates application of photodynamic therapy for noninvasive management of periodontitis without leading to bacterial resistance. Background: Periodontal diseases are one of the major causes of tooth loss in adults and are considered primarily an anaerobic bacterial infections caused by the so-called red complex species. Bacteria present in a biofilm community, enzymes, endotoxins, and other cytotoxic factors lead to tissue destruction and initiate chronic inflammation. Since many years pioneers have been working to provide logical and cost-effective therapy for management of periodontitis. Periodontal researchers have found that PDT is advantageous to suppress anaerobic bacteria. Clinical Significance: Applications of PDT in dentistry are growing rapidly. PDT application has an adjunctive benefit besides mechanical treatment at sites with difficult access. Necessity for flap surgery may be reduced, patient comfort may increase, and treatment time may decrease. The application of photosensitizing dyes and their excitation by visible light enables effective killing of periodonto-pathogens. The introduction of laser along with photosensitizers has brought a revolutionary change. Conclusion: The application of photodynamic therapy in management of periodontal diseases is very valuable. The therapy should be combined with nonsurgical periodontal therapy. Proper clinical application of photodynamic therapy can and will help patients who are systemically compromised and cannot undergo surgical therapy.